The seventh candle, and other folk tales of Eastern Europe - Einhorn, David, 1886-; Schloss, Ezekiel (New York : Ktav Publishing House, 1968)
Twenty-seven Jewish folk tales from Eastern Europe depicting village life, as well as traditional customs and beliefs.
Keywords: Tales, Jewish